Innovation in the positioning of Nutella Ferrero's product - Silva, Daniela Filipa Cerejo da (2017)
The aim of this research is to identify Nutella positioning as well as the innovation models used. This will serve two purposes: to reinforce its presence on a daily basis of the consumers and to contribute to a solid increase of sales. An exploratory study was conducted through an online survey specifically created for that purpose. The survey was elaborated based on the existing literature and Ferrero guidance. It was released through social networks (Facebook and LinkedIn), and sent via e-mail to several contacts. The results were analyzed with descriptive and Qui-square statistical methods. 607 valid answers were collected. 32,1% were Nutella shoppers and 48,9% Nutella consumers. The main motives to buy Nutella were taste, followed by brand trust. Calories and not healthy were the main motives to not buy and to not consume Nutella. Consumer analysis revealed that 28,3% of Nutella purchases were intended for children and adults, but 48% were exclusively for adults consumption. 10,5% chose Nutella for breakfast, and 12,5% assumed to consume it at breakfast. 32% considered Nutella ideal to have at breakfast, due to taste. 21% of non-consumers agreed that Nutella would be ideal for consumption at breakfast. Positioning Nutella as an everyday item at breakfast could be translated into relevant increases of Ferrero profits, since repeated consumer behavior is important for brand understanding, and also for financial motives. The overwhelming importance placed on health and the caloric composition of this product, suggests the creation of a lighter version of Nutella, with caloric reduction.